Da invisibilidade ?? conquista do espa??o social: hist??ria concisa das lutas pol??ticas e sindicais dos trabalhadores em educa????o da Universidade de S??o Paulo (1978-1988) - Hiro, C??ssio Hideo Diniz (2017)
This thesis aimed to investigate the history of the political and union struggles of workers in administrative education - and general services - of the University of S??o Paulo (USP) between 1978 and 1988. This period was marked by the resurgence of the fighting movement in the interior of the brazilian universities, which involved teachers, students and employees of these educational establishments, who emerged in the struggle against the Brazilian civil-military dictatorship, for the redemocratization of the country and for the improvement of salary, work and life conditions. This work sought to understand this historical moment from the perspective of an organized avant-garde that through the USP's Servants Association - current USP Workers' Union - acted in the most diverse internal and external struggles, standing out as one of the most combative And stiff entities in the history of the Brazilian trade union movement in the last decades of the twentieth century. Using as theoretical basis dialectical historical materialism, and the presence of authors such as Edward D. Thompson, among others, this research sought to understand the characteristics of the period investigated, the socioeconomic context, the struggles of demands and policies in the context of the public functionaries of S??o Paulo, its Union and its participation in the political processes that resulted in the fall of the civil-military dictatorship in Brazil.